2004
DOI: 10.2165/00151829-200403030-00006
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab

Abstract: Omalizumab, as add-on therapy with ICS, is an effective and well tolerated agent for the treatment of moderate to severe allergic asthma in adolescents and adults. In addition to its symptomatic and QOL benefits, omalizumab therapy allows ICS dosage reduction or discontinuation of ICS in many patients. Comparisons of omalizumab with other asthma therapies have yet to be conducted; however, clinical efficacy and tolerability data indicate that omalizumab is a valuable option in the treatment of allergic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…For 11 of 13 commercially available marketed mAbs, linear CL data were obtained from literature sources. [41][42][43][44][45][46][47][48]…”
Section: Fcrn Binding Affinity Methods Using Sprmentioning
confidence: 99%
“…For 11 of 13 commercially available marketed mAbs, linear CL data were obtained from literature sources. [41][42][43][44][45][46][47][48]…”
Section: Fcrn Binding Affinity Methods Using Sprmentioning
confidence: 99%
“…However, corticosteroids do not cure the pathology, and during extended use, it can cause systemic side effects as easy bruising and bone loss [ 6 – 8 ]. Moreover, omalizumab is used as a treatment in severely allergic asthmatics to reduce inhaled corticosteroid [ 9 ] and still adverse effects are observed [ 10 ]. Therefore, the search for news molecules for asthma prevention and/or treatment is required.…”
Section: Introductionmentioning
confidence: 99%
“…Omalizumab is a monoclonal anti-IgE antibody that was approved by the FDA in 2003 for the treatment of moderate-persistent uncontrolled allergic asthma with inhaled corticosteroids, being the first biologic used for type 2 inflammatory diseases. 13 , 15 , 16 , 17 Studies have shown improvements in asthma control, a reduction in the number of exacerbations, and a decreased need for oral corticosteroids and rescue medications. 15 In January 2021, the Brazilian National Health Surveillance Agency (ANVISA) approved omalizumab for use in Chronic Rhinosinusitis with Nasal Polyps (CRSwNP) as a complementary treatment to intranasal corticosteroids in adult patients above 18 years old.…”
Section: Omalizumab (Anti-ige)mentioning
confidence: 99%